María Cristina Lucero, La vivencia de lo festivo en la conformación de la Cristianda d , SSyCC Ediciones, Mendoza 2012, 241 pp. ISBN 978 - 950 - 9064 - 20 - 1 - Galvéz, Marcela (2016)
Fil: Galvéz, Marcela.